Pengembangan Instrumen Tes Kemampuan Berpikir Kritis Siswa Kelas VIII Pada Tema Maknanku Kesehatanku: (Development of Critical Thinking Ability Test Instruments for Class VIII Students on the Theme of My Food My Health) - Dwi Lestari; Lukman Berlian; Liska Berlian (BIODIK, 2022)
This research was conducted because there are still many students who have low critical thinking skills. This is supported by interviews conducted by researchers to 3 junior high school science teachers. One of the factors that lead to low critical thinking skills is the provision of test instruments in the form of questions that are not optimal, one form of test is a description test. The description test requires students to answer questions in the description, explanation or description in their own words and language, so that their thinking skills develop. The aims of the research were to develop and determine the feasibility of a critical thinking ability test instrument for class VIII students on the theme of my food, my health. This development research uses the Borg and Gall with the following research steps; potential and problems, data collection, product design, design validation, and design revision. The results of this study were in the form of a test instrument in the form of a description or essay test based on critical thinking skills. The description questions developed were 28 items which were validated by science experts and teachers. The average score for validation by material experts is 69%, construction experts 77%, linguists 70%, and the overall average score for science teachers is 76.6%. Therefore, the critical thinking ability test instrument developed was included in the appropriate category with an overall average score of 74% for validation. Key words: essai test, critical thinking skill Abstrak Penelitian ini dilakukankarena masih banyak ditemukan siswa yang mempunyai kemampuan berpikir kritis rendah. Hal tersebut didukung oleh wawancara yang dilakukan peneliti ke 3 guru IPA SMP. Salah satu faktor yang mengakibatkan rendahnya kemampuan berpikir kritis ialah pemberian instrumen tes berupa soal yang belum optimal, salah satu bentuk tes adalah tes uraian. Tes uraian menuntut siswa menjawab pertanyaan dalam deskripsi, penjelasan atau uraian dengan kata-kata dan bahasa sendiri, sehingga kemampuan berpikirnya berkembang. Tujuan penelitian diataranya, untuk mengembangkan serta mengetahui kelayakan instrumen tes kemampuan berpikir kritis siswa kelas VIII pada tema maakananku kesehatanku. Penelitian pengembangan ini menggunakan model Borg and Gall dengan langkah-langkah penelitian sebagai berikut; potensi dan masalah, pengumpulan data, desain produk, validasi desain, dan revisi desain. Hasil penelitian ini berupa instrumen tes berbentuk tes uraian atau esai yang berbasis kemampuan berpikir kritis. Soal uraian yang dikembangkan berjumlah 28 butir soal yang divalidasi oleh ahli dan guru IPA. Skor rata-rata validasi oleh ahli materi adalah 69%, ahli konstruksi 77%, ahli bahasa 70%, dan skor rata keseluruhan guru IPA 76,6 %. Oleh karena itu, instrumen tes kemampuan berpikir kritis yang dikembangkan Â termasukkategori layak dengan persentase skor rata-rata keseluruhan validasi yaitu 74%. Kata kunci:tesuraian, kemampuan Berpikir Kritis